Teaching Vocabulary to a Student with High Functioning Autism in an Inclusive School - Fitriatul Masitoh Fitriatul Masitoh (ELITE JOURNAL, 2022)
The goal of this study is to find out how a student with high-functioning autism (student A) at one of Surakarta's inclusive elementary schools is taught vocabulary. Case study was the method used for the study. The results of the research showed how vocabulary was taught to student A in the first grade at one of Surakarta's inclusive elementary schools, as well as the things that helped the student understand what was being taught. To sum up, English teachers who work with autistic students should: (1) use more pictures because they help autistic students learn what words mean; (2) use read-aloud events because they can help autistic students improve their pronunciation; (3) use a white board to help autistic students learn how to spell words; and (4) give more examples of how words are used in sentences to help autistic students learn how to use words.